Renewable and efficient electric power systems - Masters, Gilbert M., ....- (Hoboken : Wiley, 2004)
1 Basic electric and magnetic circuits 2 Fundamentals of electric power 3 The electric power industry 4 Distributed generation 5 Economics of distributed resources 6 Wind power systems 7 The solar resource 8 Photovoltaic materials and electrical characteristics 9 Photovoltaic systems App Sun-path diagrams App Hourly clear-sky insolation tables App Monthly clear-sky insolation tables App Solar insolation tables by city App Maps of solar insolation
Keywords: Duurzame energie; Elektrische energiesystemen